Applications Soil Observation in the Field PT. Anugerah Sumber Makmur Minamas Research Center - Hanafiah, Anggi; Wandri, Rizky; Pandini, Pandini (UIR PRESS, 2022)
Many employees still have difficulty in entering data and searching for appropriate data. Employees who still input data manually and it takes a long time. The existence of a soil observation application in the field of PT. Anugrah Sumber Makmur Minamas Research Center was created with the aim of assisting employees in entering data and searching for data quickly and accurately. This application is made using the PHP programming language and MySQL as the database. The system development method in making this application uses the design sprint method. Based on tests conducted on users, this application functionally runs as expected and the success rate is 92%.